Gene expressions involved in immune system control and serum CA125 content in polycythemia vera. Tap - Trang, Do Thi; Xuan, Nguyen Thi (Academia Journal of Biology, 2020)
Polycythemia Vera (PV) is a slowly progressing blood cancer associated with myeloproliferative neoplasms. The disease is characterized by an abnormal proliferation of three cell types including red blood cells, white blood cells and platelets and a symptom of pruritus caused by release of itching agents of activated mast cells. The enhanced expression of several genes involved in immune system control including CTLA-4, PD-1 and LAG3 are linked to activation immune tolerance. Klotho gene has anti-aging, anti-inflammation and anti-cancer functions. The SHP gene group belongs to the tyrosine phosphatase protein signaling family that regulates cancer cell proliferation through maturation, migration and apoptosis and includes two main genes, SHP-1 and SHP-2. The increased serum content of cancer antigen CA125 is considered as a cancer marker of several blood and hematopoietic disorders. In this study, we conducted experiments to determine mRNA expression of above genes in PV patients by realtime-PCR and CA125 concentration by ELISA. Results showed that expression of klotho, LAG3, CTLA-4 and PD-1 genes was decreased in PV patients, indicating that the immune tolerance was inactivated in PV patients. CA125 concentration was significantly increased in PV patients compared to healthy individuals and interestingly, there was a positive association among three patients, who having increased CA125 concentration and biochemical indicators including LDH, AST and ALT. The results in this study provide an important reference document for further studies that serve for the early detection of PV disease.